YAPON VA O‘ZBEK TILLARIDA KELISHIK VOSITALARINING FUNKSIONAL-SEMANTIK XUSUSIYATLARI - Najmiyeva Po‘lotoy Tilavmurodovna; Yuta Ujiie (International Journal of Literature and Language Studies, 2026)
The article analyzes the functional-semantic features of case-marking devices in Japanese and Uzbek. In Uzbek, case relations are mainly expressed by affixal suffixes, whereas in Japanese they are realized through case particles such as が, を, に, へ, で, と, から, より, and まで. The paper emphasizes that case markers function not only as grammatical indicators but also as units that organize discourse situation, predicate semantics, theme-rheme relations and semantic equivalence in translation.